THE THEATEROLOGICAL APPROACH TO MYTH: THE CASE OF PHAEDRA (Journal of Contemporary Philology, 2020)
This paper aims to explain the immanent connections between the myth/mythopoeic and the theatre. In the first section the definitions of the terms and subjects with which the theatre and theaterology operates with the myth are provided, and in the second section the dramatic/theatric potentials of the myth about Phaedraare presented along with its re-semantization and re-actualization in concrete drama textures. The purpose of the paper is to offer a matrix for further operationalization with the myth in its theatric sense. It also explains the systems of causalities that create the dramatic plot and the dramatic intensity, creating correlation with the myth, the mythical plot and its characteristics. Subsequently, in the main focus of this paper are the functions of the canals for re-semantisation, their purity and/or the noise in the practicability, as well as the artistic (drama) potentials of the re-semantizad (drama) text. Specifically, this text emphasizes the communication between the myth and the theatre, or even better – between the myth and the future performance text which refers to mythology and is set as specific form of re-sematisation of the semantic values from the myth and its creative elements to artistically coded type of text, i.e., performance text.
Keywords: мит; митопоетика; театрологија; Федра; реактуaлизација